Risk Mitigation Design in the Supply Chain Process of Arabica Cofee Fort Alla - Muhammad Akbar Palakbiran; Agus Mansur; Windi Auliana (Universitas Serang Raya, 2025)
The Arabica coffee supply chain in Fort Allé is subject to a number of risks that have the potential to disrupt supply continuity and product quality. The objective of this study is to identify potential risks and develop mitigation strategies that can be integrated into the value chain. The research scope encompasses the identification, prioritization, and design of field-based countermeasures. The Delphi method was employed to identify risk events and agents, and the House of Risk (HOR) approach was utilized for analysis, evaluation, and prioritization of strategies. The data collection process entailed a multifaceted approach, encompassing observational studies, in-depth interviews, the administration of questionnaires, brainstorming sessions, and focus group discussions with cooperative stakeholders. The study identified 14 risk events and 33 risk sources, leading to the formulation of 14 preventive measures. The integration of coffee crops with secondary crops was prioritized (ETDk: 5184), as it enhances both sustainability and profitability. The proposed strategies are embedded within the coffee value chain, offering practical guidance for cooperatives and agroindustry actors to strengthen supply chain resilience and increase added value. The results of this study can serve as a reference for decision-making by cooperatives, agroindustry players, and policymakers in designing coffee supply chain strengthening programs that focus on risk mitigation and increasing added value based on sustainability.